Antibiotic resistance: still a cause of concern?. Issue 3 (15th June 2021) - DeBaun, Malcolm R.; Lai, Cara; Sanchez, Mark; Chen, Michael J.; Goodnough, L. Henry; Chang, Amy; Bishop, Julius A.; Gardner, Michael J.
Abstract : Abstract: Antibiotic resistance remains a global public health concern with significant patient morbidity and tremendous associated health care costs. Drivers of antibiotic resistance are multifaceted and differ between developing and developed countries. Under evolutionary pressure, microbes acquire antibiotic tolerance through a variety of mechanisms at the cellular level. Patients after orthopaedic trauma are vulnerable to drug-resistant pathogens, particularly after open fractures. Traumatologists practicing appropriate antibiotic prophylaxis and treatment regimens mitigate infection and propagation of antibiotic resistance.